Delineating and preventing plastic waste leakage in the marine and terrestrial environment - John N. Hahladakis (14151018) (2022)
Plastics are nowadays considered to be the workhorse material of our modern society with an ubiquitous presence that has increased manifold over the past 60 years, providing several benefits to the global economy. However, inappropriate and/or uncontrolled disposal practices, poor waste management infrastructure and application of insufficient recycling technologies, coupled with a lack of public awareness and incentives, have rendered plastic waste omnipresent, littering both the marine and the terrestrial environment with multi-faceted impacts. This short communication/commentary aims at delineating the plastic litter global challenge providing, at the same time, scientific views and perspectives on properly dealing with this material type, both upstream and downstream. Other Information Published in: Environmental Science and Pollution Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11356-020-08139-y